Direct and indirect costs among employees with diabetic retinopathy in the United States - Lee, Lauren J.; Yu, Andrew P.; Cahill, Kevin E.; Oglesby, Alan K.; Tang, Jackson; Qiu, Ying; Birnbaum, Howard G. (Current medical research and opinion, 2008)
ABSTRACT Objective: To examine, from the employer perspective, the direct (healthcare) and indirect (workloss) costs of employees with diabetic retinopathy (DR) compared to control non-DR employees with diabetes, and within DR subgroups. Methods: Compared annual costs using claims data from 17 large companies (1999-2004). 'DR employees' (n = 2098) had ≥ 1 DR (International Classification of Disease, 9th Revision [ICD‑9]) diagnosis; DR subgroups included employees with diabetic macular edema (DME), proliferative DR (PDR), and employees receiving photocoagulation or vitrectomy procedures. Descriptive and multivariate tests were performed. Results: DR employee annual direct costs were $18 218 (indirect = $3548) compared to $11 898 (indirect = $2374) for controls (Δ = $2032 (adjusted); p < 0.0001). Costs differences were larger across DR employee subgroups: DME/non-DME ($28 606/$16 363); PDR/non-PDR ($30 135/$13 445; p < 0.0001); DR with/without photocoagulation ($34 539/$16 041; p < 0.0001); and DR with/without vitrectomy ($63 933/$17 239; p < 0.0001). Limitations: This study examined the incremental costs of treating DR employees, which may be higher than the incremental costs of DR itself. Some measures of diabetes severity (e.g., duration of diabetes) were not available in the claims data, and were therefore not included in the multivariate models. The cost of photocoagulation and vitrectomy procedures pertain to individuals who underwent these procedures, and not the cost of the procedures themselves. Conclusion: DR employees had significantly higher costs than controls, and larger differences existed within DR subgroups. Indirect costs accounted for about 20% of total cost.